(untitled) (Revista Nacional de Odontología, 2016)
Introduction: certain occlusal characteristics may be associated to disorders at temporomandibular joint level, esthetical alterations and functions of the stomatognathic system. They may appear at any stage of dental development and are related to several factors that include heredity, environmental issues and habits. Objective: describe the epi-demiological profile of static dental occlusion and oral habits in a group of schoolchildren in Medellin. Materials and method: descriptive transversal study in a convenience sample of 420 school students; the evaluated at a vertical plane were the vertical overbite, the edge to edge bite and the anterior open bite; at transversal plane were posterior cross-bite and scissor bite; and at sagittal level: anterior cross-bite, horizontal overbite and permanent molar and canine habits according to the Angle classification. Habits like nail biting, thumb sucking and cheilophagia were also evaluated. Results: the average was 8,7 years (± 1,8); 50,2% (211) were women; 26,4% (111) and 24,5% (103) presented canine class I relation right and left, respectively; and 63,6% (267) relation molar class I right and 61,2% (257) left. No significant statistical differences were found in the segmented analysis by gender for variables. The posterior cross-bite may be related in a significant way to the habit of thumb sucking (p = 0,010). Conclusion: dynamic occlusion studies are difficult to analyze comparatively given the variability in methodology, the control of confusing variables and the age of the patients.